A Coupled Reservoir/Wellbore Model to Simulate the Steam Injection Performance of Horizontal Wells. Issue 5 (8th May 2015) - Li, Mingzhong; Chen, Huijuan; Zhang, Yanyu; Li, Weiwei; Wang, Yiping; Yu, Meng
Abstract A coupled reservoir/wellbore model of horizontal wells in a steam injection process is presented, which considers the three‐dimensional simultaneous flow of three phases in the reservoir and gas–liquid two‐phase flow in the wellbore. Based on the model, the steam injection performance of a horizontal well is simulated. The pressure, temperature, and steam quality distribution in the wellbore as well as the steam injection profile and reservoir temperature along the horizontal wellbore are discussed. Results show that the wellbore pressure, temperature, and steam quality decrease from the horizontal wellbore heel to the toe. The steam flux rate and reservoir temperature are higher at the wellbore heel and toe. Furthermore, the variations of the steam flux rate and reservoir temperature along the wellbore increase with sustained injections, which is a disadvantage for thermal horizontal wells. Therefore, developing techniques to guarantee a uniform flow along horizontal wellbores is crucial.